Enhancing rice plant architecture and reducing lodging: A novel approach with growth regulators - Ali, Sk Asraful; Kaur, Ramanjit; Ezing, Unti Miiri; Nandipamu, Tony Manoj Kumar (Indian Farming, 2024)
Rice, a staple food for over half the world's population, faces substantial challenges in cultivation; untimely rains, hailstorms etc. leading to crop lodging being a major concern which hampers crop yield, downgrade quality and complicates harvesting. Factors like tall plants with poor tillering, improper water management, high planting density, and excessive fertilizer use contribute to lodging, exacerbated by heavy rains and strong winds. Plant growth regulators show promising results in mitigating this problem by inhibiting gibberellin biosynthesis, thereby shortening internodes and strengthening stems. Integrating plant growth regulators into comprehensive rice production systems can induce stem robustness, enhance lodging resistance, and ensure sustainable and productive rice farming.